2005
DOI: 10.1152/ajpheart.00354.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic innervation promotes vascular smooth muscle differentiation

Abstract: The sympathetic nervous system (SNS) is an important modulator of vascular smooth muscle (VSM) growth and function. Several lines of evidence suggest that the SNS also promotes VSM differentiation. The present study tests this hypothesis. Expression of smooth muscle myosin (SM2) and ␣-actin were assessed by Western analysis as indexes of VSM differentiation. SM2 expression (normalized to ␣-actin) in adult innervated rat femoral and tail arteries was 479 Ϯ 115% of that in noninnervated carotid arteries. Express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 31 publications
6
26
0
1
Order By: Relevance
“…These experiments cannot exclude the possibility that suppression by ␣-adrenergic blockade is secondary to an effect elsewhere in the animal. However, in vitro experiments have shown that ␣ 1 -adrenergic signaling can directly program smooth muscle differentiation through autocrine transforming growth factor-␤ signaling (11), while in other cell types it couples to second messengers and transcriptional pathways, including calcium (nuclear factor of activated T cells), activator protein-1, cAMP (cAMP response element binding protein), and nuclear factor-B (17,46,60). In the present study, ␣-adrenergic blockade suppressed the normal developmental maturation of MA smooth muscle and stressinduced augmentation of this process.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments cannot exclude the possibility that suppression by ␣-adrenergic blockade is secondary to an effect elsewhere in the animal. However, in vitro experiments have shown that ␣ 1 -adrenergic signaling can directly program smooth muscle differentiation through autocrine transforming growth factor-␤ signaling (11), while in other cell types it couples to second messengers and transcriptional pathways, including calcium (nuclear factor of activated T cells), activator protein-1, cAMP (cAMP response element binding protein), and nuclear factor-B (17,46,60). In the present study, ␣-adrenergic blockade suppressed the normal developmental maturation of MA smooth muscle and stressinduced augmentation of this process.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is well known that sympathetic sprouting is important for infarct healing and scar formation, especially in angiogenesis and lymphangiogenesis (3,4,20), whereas the murine HTx preparation is devoid of innervation and lacks communication with cervical ganglions and the central nervous system. Therefore, its potential impact on the inflammatory response and on cardiac neural stem cell function (10) during LV unloading cannot be clarified in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…The I group was further divided into the in situ MI (I-infarct) group and in situ sham (I-sham) group. Surviving rats were killed on days 3,7,14, and 35 after the operations.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies documented that cultured sympathetic neurons express VEGFRs and respond to VEGF by enhanced axon outgrowth and survival, 12 but so far, VEGF has not been reported to induce structural changes in prejunctional nerve terminals. Because autonomic nerve endings are known to release SMC-trophic factors, 24 a dysfunction of these nerve terminals may secondarily lead to SMC dedifferentiation. Indeed, activation of ␣ 1 -adrenoreceptors by noradrenaline stimulates SMC proliferation, 25 and sympathetic innervation increases vascular SMC contractile protein expression, 24 whereas sympathectomy results in a switch from a contractile to synthetic SMC phenotype.…”
Section: Discussionmentioning
confidence: 99%